Effects on knee joint force from a body weight load reduction system driven by rubber-less artificial muscle. Issue 5 (26th June 2019) - Saito, Naoki; Satoh, Toshiyuki; Saga, Norihiko
Abstract : Purpose: The purpose of this study is to confirm that the body weight load reduction system which is developed by us is effective to reduce the knee joint force of the walking user. This system is driven by pneumatic artificial muscle, functions as a mobile walking assist system. Design/methodology/approach: The developed body weight load reduction system driven by rubber-less artificial muscle (RLAM) was tested experimentally. Simple force feedback control is applied to the RLAM. The system moves as synchronized with vertical movement of the walking user. The knee joint force during walking experiments conducted using this system is estimated by measurement of floor reaction force and position data of lower limb joints. Findings: The knee joint force during walking is reduced when using this system. This system contributes to smooth change of knee joint force when the lower limb contacts the floor. Practical implications: This lightweight body weight load reduction system is particularly effective for realizing easy-to-use mobile walking assist system. Originality/value: A lightweight body weight load reduction system using pneumatic artificial muscle is a novel proposal. Additionally, these new evaluation results demonstrate its effectiveness for reducing knee joint force during walking.